1981
DOI: 10.1002/1097-0142(19810101)47:1<156::aid-cncr2820470127>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyosarcoma of the skin and subcutaneous tissue

Abstract: In a study of 65 primary cutaneous leiomyosarcomas and 15 primary superficial subcutaneous leiomyosarcomas, tumors occurred at any age but were more common in middle age and most common on the extremities. They developed as solitary painful or tender intracutaneous or subcutaneous nodules. Microscopically, the cutaneous leiomyosarcomas consist of a poorly delineated proliferation of spindle-shaped atypical myomatous cells arranged in interlacing fascicles which merge into collagenous stroma. Subcutaneous leiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
304
5
29

Year Published

1984
1984
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 330 publications
(345 citation statements)
references
References 15 publications
7
304
5
29
Order By: Relevance
“…It is well known that an adequate surgical margin is the most important factor for local control. 9,10,13,29,31,39,40 Our multivariate analysis identified no statistical correlation between local treatment and metastasis or overall survival. This finding is in line with other reports.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…It is well known that an adequate surgical margin is the most important factor for local control. 9,10,13,29,31,39,40 Our multivariate analysis identified no statistical correlation between local treatment and metastasis or overall survival. This finding is in line with other reports.…”
Section: Discussionmentioning
confidence: 74%
“…In our series, none of the cutaneous tumors metastasized during follow-up, and none of the patients with cutaneous tumors died from tumorrelated causes, consistent with previous studies, which have shown that strictly cutaneous LMS hardly ever metastasizes. 9,10,18,19,23,26,27,37 At the histopathologic review, we designated 8 tumors (3 in patients who had been referred after recurrence) that extended into both cutis and subcutis as subcutaneous tumors, because their growth pattern denied classification as cutaneous tumors. However, none of these tumors metastasized during follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same criterion is used in humans to differentiate dermal leiomyomas from leiomyosarcomas. 3,4 Dermal leiomyosarcomas in these ferrets were well differentiated, and most neoplastic cells had the cytologic appearance of smooth muscle fibers. Consistent with well-differentiated neoplasms, excision was curative in all 5 animals for which a follow-up was available.…”
mentioning
confidence: 92%
“…Fields e Helwig (8) trataram 59 pacientes com LMS cutâneo usando ressecção conservadora ou ressecção local e encontraram taxa de recorrência de 42%. Entretanto, lesões recorrentes ou residuais que foram totalmente excisadas, geralmente não apresentaram recidiva local nem metástases, ou estavam relacionadas à causa da morte desses pacientes.…”
Section: Discussionunclassified